SEED TREATMENT BETWEEN STORAGE PERIOD FOR INCREASING THE STORABILITY OF CHILI (Capsicum annuum L.) SEED - Sari, Maryati; Permatasari, Arinda Ayu; Permatasari, Okti Syah Isyani (Universitas Trilogi, 2025)
Chilli seed is rather expensive, so it should be saved in controlled storage. In marketing, seeds may be exposed in the ambient room that is optimum for fungi activities. Between storage periods seed treatment is expected can increase chilli seed vigor and seed storability in ambient storage. This research aimed to obtain the proper between-storage period seed treatment that can increase chili seed vigor and seed storability. The research was conducted at the Laboratory of Seed Quality Testing and Storage, and Seed Health Laboratory, Department of Agronomy and Horticulture IPB, from February to August 2023. Bogor. The study used a completely randomized split-plot design. Seed lots were the main plot, consisting of two levels, namely (1) lot 2017 and (2) lot 2021. The between-storage period seed treatment was as subplots consisting of five levels, namely (1) control, (2) rinsing, (3) sun-drying, (4) oven, and (5) fungicide. The results showed that chili seeds without between storage periods seed treatments were still able to maintain viability until the end of storage (germination rate of 80% in a 0-month storage period to 73.3% in a 6-month storage after treatments). Washing, sun-drying, and oven treatments have the potential to maintain chili seed vigor better than controls based on the radicle emergence (RE).